Harnessing Digital Financial Services: Unlocking the Path to Enhanced Financial Performance and Inclusivity in Indonesia’s Banking Sector - DEWI CAHYANI PANGESTUTI (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Objective: This study aims to analyze the impact of digital financial services, digital financial inclusion, and service usage on the financial performance of national private commercial banks in Indonesia. The research identifies the dimensions of financial inclusion that most significantly affect the financial performance of banks. Design/Methodology/Approach: This study adopts a quantitative approach using panel data from 43 banks listed in Indonesia during the period from 2019 to 2024. Regression analysis is conducted to explore the relationship between independent variables, such as digital financial services, accessibility, availability, and service usage, on financial performance, measured by Return on Assets (ROA). Findings: The results indicate that the usage of digital financial services and the accessibility of services have a significant positive effect on financial performance, while the availability of physical infrastructure, such as bank branches and ATMs, does not significantly affect financial performance. Increased usage of digital financial services and greater accessibility for the public contribute to enhanced profitability and operational efficiency in banks. Research Limitations/Implications: The limitations of this study include the scope of data, which is limited to national private commercial banks in Indonesia over a specific period, meaning the findings may not fully reflect the banking sector outside of this scope. This study also suggests further research to explore additional factors that may influence bank financial performance, such as digital literacy and regulatory policies that support technology adoption. Practical Implications: The findings of this study can be applied by banking practitioners and policymakers to design more effective strategies for optimizing digital infrastructure and financial inclusion to enhance bank performance. Banks should focus on improving digital services and ensuring broader access to banking services for the public to maximize their utilization. Originality/Value: This study makes a unique contribution by deepening the understanding of the relationship between digital financial inclusion and bank financial performance in Indonesia, particularly by considering accessibility, availability, and service usage. It enriches the existing literature by providing empirical evidence on the importance of digital transformation in banking to improve financial performance. Keywords: Digital Financial Services, Accessibility, Availability, Service Usage, Financial Performance, Financial Inclusion. Paper Type: Research Paper